Chloroplast and mitochondrial genomes of tomato - Lichtenstein, Gabriel (2016)
This chapter summarizes the main features of the tomato plastid and mitochondrial genomes in the context of the current knowledge about “orthologue” genomes from other higher plants species in a historical perspective. We have focused on the application of this knowledge to aid in deciphering the functional roles of these organelles in growth and developmental processes of the tomato plants, especially on those related to fruit ripening. It also presents an assessment of the phylogenetic position of tomato, based on the available information of plastid and chondrome sequences from other land plants; which adds to the understanding of the evolutionary history of plants.